Multi-parametric approach to assess combined effects of pollution and climate change in West African aquatic ecosystems - (:unkn) unknown (My University, 2011)
In the last decades, West African aquatic ecosystems were strongly impacted by climate change inducing increase of water salinity, and by anthropic activities such as industry, agriculture and intensive fisheries that discharge chemical pollutant in environment. To assess the combined effects of both environmental changes, a multiparametric approach was performed. For this purpose, Black chinned Tilapia (Sarotherodon melanotheron) were sampled during dry and rain period in 8 sites characterized by various contamination and salinity profiles. Levels of pollution by PAHs, PCBs, OCPs in sediments of eight sampling sites were characterized. A set of biochemical biomarkers including biotransformation enzymes (EROD activity and glutathione-S-transferase), oxidative stress indicator (lipoperoxidation), neurotoxicity end-point (brain acetylcholinesterase) and estrogenicity biomarker (circulating vitellogenin) was measured to understand the effects of contamination. Moreover, physiological parameters such as growth rate, condition factor and gonado- somatic index were measured in all tilapia to provide data on effect of environmental conditions on fish physiology. The results of this work shows that the health fish living in West African aquatic ecosystems is impacted by combined effects of chemical pollution and climate change and argue for a better assessment of these ecosystems to prevent furthers degradation.
Keywords: African Research